Rancang Bangun Sistem Informasi untuk Menunjang Penyusunan Laporan Keuangan pada Farm Layer Raja Telur - hedi pandowo (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2018)
Post amnesty tax that has been rolled out by the government encourages some business people to compile tax reports in bookkeeping. Farm layer is an industry that is engaged in the production of eggs, is one of the business people with the requirements of reporting tax books. The important thing in the presentation of financial statements to support tax reporting is the availability of adequate human resources and the ability to process data quickly and accurately. In general, business people in the field of farm layer data processing process only on recording data recording and only contains recapitulation of population growth costs. Of course this has not been sufficient for the purposes of preparing financial statements.These problems can be solved by creating a computer application program that functions to accommodate all the activities in the farm layer company. With this computer application program, it is expected that all data management from beginning to end is recorded in detail and is able to produce financial reports quickly and accurately.Â Keywords: Farm Layer, Recording, Financial Reports, Computer Application Programs